Funções do cálcio nuclear e citosólico na sinalização celular - Dawidson Assis Gomes (2006)
Nucleoplasmic and cytoplasmic calcium (Ca2+ ) can be regulated independently. The relative contribution of nucleoplasmic and cytoplasmic Ca2+ to biological processes such as gene transcription, cell growth, apoptosis and cell cycle control remain to be -binding proteins fully defined. In order to address this question, we target the Ca2+ parvalbumin (PV) or calretinin (CR), to either the nucleus or cytoplasm as a molecular tool to selectively buffer either nucleoplasmic or cytoplasmic Ca . These data showed that expression of targeted PV or CR was sufficient to buffer Ca2+ signals in these respective sub-cellular compartments. The PV constructs were delivered by adenovirus . The construct ad-PV-NES (ad) to explorer the functions of nuclear and cytosolic Ca2+ (Nuclear Exclusion Signal) blocked the phosphorylation of Erk1 and expression of p38. In contrast, the construct ad-PV-NLS (Nuclear Localization Signal) blocked the phosphorylation of cyclin dependent cinase 1 (CDK1). We also investigated the mechanisms responsible for InsP3 generation within the nucleus. In order to address this question, we employed an InsP binding protein (InsP3 Sponge) as a molecular tool to . SkHep1 cells expressing selectively buffer either nucleoplasmic or cytoplasmic InsInsP3 Sponge in the nucleus blocked the Ca2+ response induced by Hepatocyte Growth response in the cells was not affected by stimulation with factor (HGF), while the Ca2+ arginine vasopressin (AVP). In contrast, expression of InsP3 Sponge in the cytoplasm blocked the Ca2+ response induced by AVP, but the Ca2+ response induced by HGF was not affected. In addition, stimulation with HGF induced translocation of c-met to the nucleus and let to the presence of phospholipase C (PLCy) as well within the nucleus. and Ca2+ signals, In summary, these results show that HGF can generate nuclear InsP3and that this likely results from translocation of c-met and PLCy to the nucleus. Since signals in the nucleus and cytoplasm have distinct effects on expression and Ca2+ activation of cinases and transcription factors, these observations about c-met trafficking and function reveal one mechanism by which Ca2+ signals can be compartmentalized to obtain these distinct cellular effects.